2016
DOI: 10.1002/esp.3947
|View full text |Cite
|
Sign up to set email alerts
|

Complexities of landscape evolution during incision through layered stratigraphy with contrasts in rock strength

Abstract: Variation in the erodibility of rock units has long been recognized as an important determinant of landscape evolution but has been little studied in landscape evolution models. We use a modified version of the Channel-Hillslope Integrated Landscape Development (CHILD) model, which explicitly allows for variations in rock strength, to reveal and explore the remarkably rich, complex behavior induced by rock erodibility variations in even very simple geologic settings with invariant climate and tectonics. We stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
217
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 116 publications
(234 citation statements)
references
References 97 publications
(132 reference statements)
17
217
0
Order By: Relevance
“…For S ct ≥ S t , the topography follows bedding planes (a dip-slope). Similar to cliffs on threshold hillslopes, over-steepened knickzones form because of a tendency for undermining at strong-over-weak contacts (Forte et al, 2016). Erosion rate amplification in the channel network As Perne et al (2017) demonstrated, the formation of oversteepened knickzones in channels where weak rocks underlie strong rocks is analogous to the threshold hillslope problem discussed earlier.…”
Section: Amplification Of Erosion Ratesmentioning
confidence: 71%
See 3 more Smart Citations
“…For S ct ≥ S t , the topography follows bedding planes (a dip-slope). Similar to cliffs on threshold hillslopes, over-steepened knickzones form because of a tendency for undermining at strong-over-weak contacts (Forte et al, 2016). Erosion rate amplification in the channel network As Perne et al (2017) demonstrated, the formation of oversteepened knickzones in channels where weak rocks underlie strong rocks is analogous to the threshold hillslope problem discussed earlier.…”
Section: Amplification Of Erosion Ratesmentioning
confidence: 71%
“…This contrast dictates that the rate of horizontal retreat below the contact (celerity of the weak layer, C ew ) will tend to be faster than above the contact (celerity of the strong layer, C es ) and thus undermining is expected. As a result, a near-vertical waterfall forms and grows steadily in height (m) during knickzone retreat, eventually occupying the full extent of each strong-weak couplet (Forte et al, 2016;Perne et al, 2017). Where n ≠ 1, the rate of horizontal retreat depends on stream gradient (Equation (4)).…”
Section: Amplification Of Erosion Ratesmentioning
confidence: 99%
See 2 more Smart Citations
“…The stratigraphic order of rock units, their erodibility, and their orientations and dips are fundamental controls of landscape development (Forte et al, 2016). Alberti et al (2013) described a method to distinguish river terrace levels based on rock clast hardness and degree of weathering measured with an Equotip.…”
Section: Fluvial Landformsmentioning
confidence: 99%